Species richness, classification and a checklist of the grasses (Poaceae) of Mexico - Sánchez Ken, Jorge Gabriel (Instituto de Ecología, A.C., 2018)
Background and Aims: In 2006 the catalogue of the grasses of Mexico was published, but since then, the classification as well as new species to science changed the numbers of the family in Mexico and worldwide. The main objective of this study is to update the checklist of taxa in Mexico through the consolidation of many online databases. Other objectives include the comparison of the species richness of the family Poaceae between the richest countries, as well as to analyze the taxa richness at state level and by taxonomic categories.Methods: National and foreign online databases that included Mexican vouchers were downloaded and curated, as well as a visual confirmation of the identity of a great percentage of specimens. Names of the species, states where they were collected, and the herbaria acronyms were annotated. The resulting database was complemented only with literature from 2006 to the current year and that not included in the catalogue that showed vouchers.Key results: A total of 1416 taxa were accounted for 227,973 records, these include 215 genera, 1312 species and 214 infraspecific categories. Of the total number of species, 1092 are considered native and 224 introduced (cultivated and/or weed). There are 304 (27.83%) endemic species or 311 (28.10%) if infraspecific categories are considered. In México, the subfamilies most diverse are the Panicoideae, Chloridoideae and Pooideae, that together add up 183 genera and 1175 species, the remaining subfamilies have a minor number of taxa.Conclusions: Nominally, Mexico occupies the 5th place in species richness; however, considering the geographical extension of each country, Mexico ascends to the 1st place as the worldwide richest country of native and introduced grass species by km2. At the state level, the smallest states are the most species-rich.